Mathematics Learning Strategies to Improve Critical Thinking and Problem-Solving Skills for Madrasah Ibtidaiyah Students - Ratnasari, Khurin'In; Sholihah, Mar'atus; Asnawan, A; Efendi, Erfan; Sutrisno, Nina (Proceedings International Conference on Education Innovation and Social Science, 2022)
Critical thinking and problem-solving skills are very important for students to have both in the short and long term. However, in reality, students in madrasah ibtidaiyah have the low-level category of critical thinking and problem-solving skills. For this reason, it is necessary to have the right strategy to be able to improve these two abilities. This scientific article will answer the question of how mathematics learning strategies can improve critical thinking and problem-solving skills in madrasah ibtidaiyah students. By using descriptive qualitative methods and using library research in collecting data and information. Problem Based Learning can be the right strategy or model to achieve these goals. In addition, by integrating Problem Based Learning and IDEAL (identify, define, enumerate, analyze, list, and self-correct). This is because the strategy emphasizes the involvement of students in the process of solving a problem. Thus, students no longer depend only on the teacher but can also independently find solutions to the problems they are facing.